2000
DOI: 10.1093/ptr/10.4.435
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Patterns and Working Alliance in Trauma Therapy for Victims of Political Violence

Abstract: We examined the development of alliance in therapy in different attachment groups in a naturalistic setting. The participants were 36 self-referred Palestinian political ex-prisoners, who were victims of torture and ill treatment and had sought psychotherapy. Their therapy lasted for 10-12 months. The analyses showed that the development of alliance during therapy followed different patterns across the attachment groups. Yet early alliance did not differ between the groups. For the autonomous individuals, alli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 38 publications
2
52
0
6
Order By: Relevance
“…Specifically, a line of research has developed that explores the role of attachment style in predicting alliance levels and growth in alliance throughout group treatment. Several groups have reported that attachment insecurity and attachment avoidance are associated with distinct patterns in alliance development (Chen & Mallinckrodt, 2002; Kanninen, Salo, & Punamäki, 2000). In a finding that highlights the layered nature of alliance formation, Tasca and colleages (2007) found that patients’ attachment styles moderated their rate of alliance growth in a psychodynamically-oriented group treatment (GPIP) but not in GCBT.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a line of research has developed that explores the role of attachment style in predicting alliance levels and growth in alliance throughout group treatment. Several groups have reported that attachment insecurity and attachment avoidance are associated with distinct patterns in alliance development (Chen & Mallinckrodt, 2002; Kanninen, Salo, & Punamäki, 2000). In a finding that highlights the layered nature of alliance formation, Tasca and colleages (2007) found that patients’ attachment styles moderated their rate of alliance growth in a psychodynamically-oriented group treatment (GPIP) but not in GCBT.…”
Section: Discussionmentioning
confidence: 99%
“…They showed, as do our results, that the working models of secure individuals involved benign perceptions and a sense of inner strength that facilitated effective coping with traumatic stress, whereas insecure-preoccupied individuals exaggerated the significance of the threat and negative perceptions, and felt personally inadequate and helpless in dealing with the stress. Findings among Israeli prisoners of war (Solomon, Ginsburg, Mikulincer, Neria, & Ohry, 1998), civilians under bombardment (Mikulincer, Florian & Weller, 1993) and among Palestinian political prisoners (Kanninen, Salo, & Punamäki, 2000) show that attachment style also explains individual differences in mental health, particularly under conditions of high stress. These results suggest that the attachment-specific, unique inner working models as well as memory representations serve the function of integrating and assimilating new and painful experiences into existing life histories (Cason, Resick, & Weaver, 2002;Horowitz, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…haben in einer Stichprobe traumatisierter politischer Gefangener beschrieben, dass die Bindungssicherheit insbesondere im Zusammenhang mit schweren Traumatisierungen die Entwicklung positiver Beziehungen zu anderen fördert und die Prä-valenz negativer Emotionen mindert, also einen wichtigen Schutzfaktor darstellt. Aus derselben Arbeitsgruppe wird allerdings berichtet(Kanninen et al 2000), dass sicher gebundene Opfer politischer Verfolgung insbesondere für psychischinterpersonale Traumatisierungen vulnerabler waren, während unsicher gebundene Personen als anfälliger für körperliche Traumatisierungen beschrieben werden. Neben Bindungssicherheit wurde in einer Untersuchung von traumatisierten Mitarbeitern des Belgischen Roten Kreuzes vonDeclerq u. Palmanns (2005) soziale Unterstützung als Moderatorvariable im Zusammenhang mit der Entstehung von PTSD-Symptomen nach schweren Traumatisierungen beschrieben.In der sozialpsychologischen Literatur hat sich in jüngster Zeit eine Diskussion darüber entwickelt, ob Bindungsvermeidung im Zusammenhang mit Traumatisierungen eher als Schutz-oder als Risikofaktor zu verstehen sei.…”
unclassified